ANALISIS INCOME STATEMENT DI BANK SYARIAH MANDIRI CABANG BANDUNG PERIODE 2005-2011 - Dede Hertina (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
ABSTRACTThis research was conducted at the Bank Sharia Mandiri Bandung. In era globalization like in a moment all business included world banking participate contribution in nation building economic. In give image positive at world banking to investors and specially for third party prime things must know is financial statement. One of the type from financial statement is income statement that is of a urgent information about rate of return and net profit for one a particular period. The phenomenon that occurs is decreasing and increasing profit situation so made return at buy-sales more increase.The purpose of this study is to find progress income and to find solution/constraint that fight Bank Sharia Mandiri in order to defend rate of profit.The method used in this research are descriptive quantitative method. With used progress income could find that rate of profit in Bank Sharia Mandiri Bandung experience of decreasing and increasing every year.The results showed that income in Bank Sharia Mandiri Bandung tended to experience decreasing and increasing profit. Rate of return increased caused by miss strategic of marketing that used so needed fund from loss elimination in last year. Whereas profit increasing caused by collection occurs all current account carry BSM has bonus from Sertificate Bank Indonesian Sharia (SBIS).Keywords : Financial Statement and Income Statement